New work ethics?: The corporate athlete's Back End Index and organizational performance - Kelly, P; Allender, S; Colquhoun, D (2007)
Drawing on Michel Foucault's later genealogies of the Self the paper will illustrate particular dimensions of the increasingly powerful individualizing and normalizing processes shaping the lifeworlds of worker-citizens in a globalizing risk society. Processes that require those who wish to be positively identified as professional, entrepreneurial, resilient, effective, athletic to do particular sorts of work on themselves. Here the paper argues that we can identify the emergence of what we call New Work Ethics. We illustrate this more general argument via an analysis of the ways in which a large Information Technology (IT) organization seeks to produce - via a workplace health and fitness program - employees who imagine themselves as embodying the behaviours and dispositions that mark the person as a corporate athlete. Knowledge of the Self in these terms can, it is promised, enhance the performance of the Self, and the organization. Copyright © 2007 SAGE.